Halal Critical Point of Beneng Taro Products Identification Produced by Micro Enterprise in Serang City, Banten - Fitria Riany Eris; Zulfatun Najah; Tubagus Bahtiar Rusbana; Puji Wulandari; Nurul Annadzifah; Rifqi Ahmad Riyanto (University of Sultan Ageng Tirtayasa, 2023)
Food products that have a halal certificate must fulfill halal standards. The halal assurance system is created and implemented in order to ensure the halal production process. The concept of Halal Assurance System (HAS) 23000 is used as a reference to implement halal product processing. The problem is that there are many ingredients, the main raw materials and additional ingredients—that are not clear about their origin and halal assurance. This study aims to identify the Halal Critical Point (HCP) of derivative of beneng taro produced by microenterprises. This study uses a qualitative method. Sources of research data were taken from observations and interviews with owners of businesses, as well as observations at the research location. Halal critical materials are beneng taro flour, cassava flour, vegetable oil, and dry coriander. Halal critical processes are production, washing facilities, and transportation. The critical control points in production include soaking, washing, and frying.